The Effect of Risk Factor Disclosures on the Pricing of Credit Default Swaps - Chiu, Tzu‐Ting; Guan, Yuyan; Kim, Jeong‐Bon (Contemporary Accounting Research, 2018)
ABSTRACT This study examines the relation between narrative risk disclosures in mandatory reports and the pricing of credit risk. In particular, we investigate whether and how the Securities and Exchange Commission ( SEC ) mandate of risk factor disclosures ( RFD s) affects credit default swap ( CDS ) spreads. Based on the theory of Duffie and Lando (2001), we predict and find that CDS spreads decrease significantly after RFD s are made available in 10‐K/10‐Q filings. These results suggest that RFD s improve information transparency about the firm's underlying risk, thereby reducing the information risk premium in CDS spreads. The content analysis further reveals that disclosures pertinent to financial and idiosyncratic risk are especially relevant to credit investors. In cross‐sectional analyses, we document that RFD s are more useful for evaluating the business prospects and default risk of firms with greater information uncertainty/asymmetry. Overall, our findings imply that the SEC requirement for adding a risk factor section to periodic reports enhances the transparency of firm risk and facilitates credit investors in evaluating the credit quality of the firm.